Using social capital to address youth sexual and reproductive health and rights in disaster preparedness and response: A qualitative study highlighting the strengths of Pacific community organisations and networks. - Nabreesa Murphy; Peter Azzopardi; Kathryn Bowen; Phoebe Quinn; Tamani Rarama; Akanisi Dawainavesi; Meghan A Bohren (Public Library of Science (PLoS), 2023)
In the Pacific region, youth sexual and reproductive health and rights (SRHR) are strongly influenced by sociocultural and structural factors, which limit access to SRHR information and services for youth. As climate-related disasters intensify in the Pacific, existing challenges to youth SRHR may increase the risk of worse SRHR experiences and outcomes for youth before, during and after disasters. Community-based models of SRHR service provision models increase accessibility for youth in non-disaster times, but there is limited evidence of how community organisations address youth SRHR in disaster contexts. We conducted qualitative interviews with 16 participants from community organisations and networks in Fiji, Vanuatu, and Tonga following the 2020 Tropical Cyclone (TC) Harold. Guided by the Recovery Capitals Framework (natural, built, political, cultural, human, social, and financial capitals), we explored how community organisations addressed challenges to facilitate access to youth SRHR information and services. Social capital in the form of peer networks and virtual safe spaces was used to navigate challenges in political, financial, and natural capitals. Existing relationships and trusted collaborations were crucial to address cultural taboos related to youth SRHR. Previous experiences of disasters and knowledge of contexts enabled participants to provide sustainable solutions to identified SRHR needs. The work conducted by community organisations and networks pre-disaster made it easier to identify and address youth SRHR risks following disasters. Our research offers a unique perspective into how social capitals were used to mitigate challenges to youth SRHR across natural, human, financial, cultural, built, and political capitals. Findings offer important opportunities to invest in existing community strengths, for transformative action to advance the SRHR of Pacific youth.